(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In recent years, in most foreign countries, the development of the national tax policy and the implementation of it, along with the emphasis on the processes of optimal distribution of the tax burden on the basis of ensuring the financial harmony of the budget and taxpayers, are strengthening the tendency to stimulate scientific research in this regard. In addition, in many scientific centers, the tax burden and its impact on the economy in relation to the gross domestic product, price, inflation, investment, labor and consumer market are given high priority to scientific researches.